Evolution of Neural Net Architectures by a Hierarchical Grammar-Based Genetic Systems - Jacob, Christian; Rehder, Jan (Artificial Neural Nets and Genetic Algorithms - Proceedings of the International Conference (ICANNGA'93), 1993)
We present a hierarchically structured system for the evolution of connectionist systems. Our approach is exemplified by evolution paradigms for neural network topologies and weights. Our descriptions of a network’s connectivity are based on context-free grammars which are used to characterize signal flow from input to output neurons. Evolution of a simple control task gives a first impression about the capabilities of this approach.
UnivIS-Import:2015-04-16:Pub.1993.tech.IMMD.IMMD2.evolut